PEMBELAJARAN DENGAN PENDEKATAN METACOGNITIVE GUIDANCE (MG) UNTUK MENINGKATKAN LITERASI MATEMATIS SISWA SMP - Elsa Komala; Siti Nur Sabila Qintani (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractTo the effect this research is subject to see the improvement of students' mathematical literacy by using the Metacognitive Guidance (MG) approach, especially the mathematical literacy ability of level 3 and level 4 students. The design of this research is non-equivalent control group design. The experimental class is given by using the Metacognitive Guidance (MG) approach and the control class given the learning with the conventional approach. The population in this study is all students of class VII of one of the Junior High School in Cianjur. The samples were chosen as many as 2 classes from eight existing classes with purposive sampling technique. To obtain the result of research data using instrument in the form of mathematical literacy level 3 and level 4, and student questionnaire. Data processing increased the ability of mathematical literacy using mann-witney test. Based analisi data,  the results showed that the improvement of students 'mathematical literacy skills using the Metacognitive Guidance (MG) approach was better than the improvement of students' mathematical literacy skills using conventional approach, the improvement was in the medium category. The questionnaire results show that students' attitude toward mathematics learning using Metacognitive Guidance (MG) approach is positive.Keywords: Metacognitive Guidance Approach, Mathematical Literacy